2014
DOI: 10.1371/journal.pone.0089119
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Insecticide Use in Broad-Acre Grains Production: An Australian Study

Abstract: Prophylactic use of broad-spectrum insecticides is a common feature of broad-acre grains production systems around the world. Efforts to reduce pesticide use in these systems have the potential to deliver environmental benefits to large areas of agricultural land. However, research and extension initiatives aimed at decoupling pest management decisions from the simple act of applying a cheap insecticide have languished. This places farmers in a vulnerable position of high reliance on a few products that may lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…For example, women who gained access to novel, female-initiated prevention methods, such as microbicide gel, during other research trials reported the need to seek consent from their sexual partners in order to use them (C. M. Montgomery et al, 2008; van der Straten et al, 2014; Woodsong & Alleman, 2008). The findings presented here indicate that men’s desire for unprotected sexual encounters may directly conflict with the behavior change required for risk reduction even when the male partner is the one who would benefit most from that risk reduction strategy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, women who gained access to novel, female-initiated prevention methods, such as microbicide gel, during other research trials reported the need to seek consent from their sexual partners in order to use them (C. M. Montgomery et al, 2008; van der Straten et al, 2014; Woodsong & Alleman, 2008). The findings presented here indicate that men’s desire for unprotected sexual encounters may directly conflict with the behavior change required for risk reduction even when the male partner is the one who would benefit most from that risk reduction strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Using the ET approach as the measure of impact can address the request by several researchers that the gap needs to be filled between natural pest control, crop damage, and crop yield (Cullen et al ., ; Jonsson et al ., ; Bommarco et al ., ). The results from studies that have evaluated yield in relation to natural pest control are quite variable (Macfadyen et al ., ). In part this may be due to the nonlinear relationship between yield, insect density, and insect damage.…”
Section: Capturing Pest Control From Habitats Surrounding Crop Fieldsmentioning
confidence: 97%
“…Naturally, insufficient feeding leads to reduced ability for reproduction (Böttger et al, 2013), so the long term prospects are poor for the detritivore populations affected. To many regulators of chemicals, whether mayflies or other macroinvertebrates are depleted is not important, or at least not as much as the increase in productivity that farmers may obtain from using products like neonicotinoids, although the latter benefits are questionable-see (Seagraves and Lundgren, 2012;Macfadyen et al, 2014). Just because macroinvertebrates are not seen, since they are small and live at the bottom of ponds and streams, this does not mean they can be dispensed with.…”
Section: Reduced Decomposition Capacitymentioning
confidence: 99%